2012
DOI: 10.1590/s0100-879x2012007500129
|View full text |Cite
|
Sign up to set email alerts
|

Role of p53 codon 72 polymorphism in chromosomal aberrations and mitotic index in patients with chronic hepatitis B

Abstract: Polymorphisms of the p53 gene, which participates in DNA repair, can affect the functioning of the p53 protein. The Arg and Pro variants in p53 codon 72 were shown to have different regulation properties of p53-dependent DNA repair target genes that can affect various levels of cytogenetic aberrations in chronic hepatitis B patients. The present study aimed to examine the frequency of chromosomal aberrations and the mitotic index in patients with chronic hepatitis B and their possible association with p53 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…However, isolated anti-HBc refers to the presence of anti-HBc in the serum without HBsAg or HBsAb and that is because of the resolved HBV infection, due to that HBsAb had declined to the undetectable level. HBV testing during the window period or chronic infection, HBsAg cannot be detected due to protein mutation which makes it undetectable by certain diagnostic assays (Akbaş et al, 2012). In this study, our results indicated that the HBV serological markers, such as HBeAg, HBcAg and Anti-HBe were significantly decreased in HCC and cirrhosis groups compared to chronic group (P = 0.022, P = 0.001 and P = 0.041, respectively).…”
Section: Controlmentioning
confidence: 59%
“…However, isolated anti-HBc refers to the presence of anti-HBc in the serum without HBsAg or HBsAb and that is because of the resolved HBV infection, due to that HBsAb had declined to the undetectable level. HBV testing during the window period or chronic infection, HBsAg cannot be detected due to protein mutation which makes it undetectable by certain diagnostic assays (Akbaş et al, 2012). In this study, our results indicated that the HBV serological markers, such as HBeAg, HBcAg and Anti-HBe were significantly decreased in HCC and cirrhosis groups compared to chronic group (P = 0.022, P = 0.001 and P = 0.041, respectively).…”
Section: Controlmentioning
confidence: 59%
“…(10,17) Knowing the diagnostic o the patients, infected with HCV, medical specialists could aplay the proper treatment. (14,15) HCV infection affect both genders, male and female in specially adults. (3,9)There are known patients diagnosed with HCV, also with comorbidities.…”
Section: Introductionmentioning
confidence: 99%